2014
DOI: 10.1111/jdv.12689
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐margin excision is a safe, reliable treatment for well‐defined, primary pigmented basal cell carcinoma: an analysis of 288 lesions in Japan

Abstract: Surgical excision with a 2-3-mm margin is reliable treatment for well-defined, primary pigmented BCC, with a complete removal rate of 99%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 15 publications
2
40
0
10
Order By: Relevance
“…Exceptions may be made for small, well‐defined nodular BCC (nBCC) and pigmented BCC lesions. Here, complete removal is achieved in almost all cases with narrow surgical margins of 2 to 3 mm . If microscopically controlled surgery is not available, tumors with a high recurrence risk (Table ) should be removed using conventional excision with surgical margins of more than 5 mm.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Exceptions may be made for small, well‐defined nodular BCC (nBCC) and pigmented BCC lesions. Here, complete removal is achieved in almost all cases with narrow surgical margins of 2 to 3 mm . If microscopically controlled surgery is not available, tumors with a high recurrence risk (Table ) should be removed using conventional excision with surgical margins of more than 5 mm.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Zur Rezidiv‐Vermeidung sollten bei Tumoren mit niedrigem Rezidivrisiko Sicherheitsabstände von 3 bis 5 mm geplant werden. Ausnahmen können kleinere scharf abgrenzbare noduläre Basalzellkarzinome (nBZK) und pigmentierte BZK darstellen, in denen auch mit knappen Resektionsrändern von 2 bis 3 mm eine vollständige Entfernung in nahezu allen Fällen erreicht werden kann . Bei Tumoren mit hohem Rezidivrisiko (Tabelle ), in denen keine mikroskopisch kontrollierte Chirurgie verfügbar ist, sollte der Sicherheitsabstand bei konventioneller Exzision über 5 mm liegen.…”
Section: Chirurgische Therapieunclassified
“…Neuere Daten von Arits et al. zeigen in einer Vergleichsstudie zwischen MAL‐PDT, Imiquimod und 5‐FU, dass 5‐FU in der Behandlung von sBZK etwa gleich effektiv wie MAL‐PDT, jedoch Imiquimod unterlegen ist (Tumorfreiheit nach 12 Monaten: 72,8 % [95 %‐KI 66,8–79,4] für MAL‐PDT, 83,4 % für Imiquimod, 80,1 % …”
Section: Topische Therapieunclassified
“…3 These strategies are based on studies in the Caucasian population on primary and recurrent BCCs that arise as non-pigmented lesions and/or with poorly defined clinical tumour borders. 4 However, in Asians, most BCCs tend to originate as pigmented lesions (52.4%-90%) with well-defined clinical tumour borders. [4][5][6] Additionally, the local recurrence rates are low after complete excision even with close margins.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, in Asians, most BCCs tend to originate as pigmented lesions (52.4%-90%) with well-defined clinical tumour borders. [4][5][6] Additionally, the local recurrence rates are low after complete excision even with close margins. In a cohort of Japanese patients with BCC, Takenouchi et al 6 reported that the 5-and 10-year recurrence rates after complete excision without use of MMS were 0.4% and 0.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%